Color Variability of Cosmopolitan Beetles in Mindanao, Philippines - Ernel Bagbag; Mark Anthony J. Torres; Cesar G. Demayo (Andalasian International Journal of Entomology, 2024)
Beetles (Insecta: Coleoptera) stands out as one of the most diverse insect groups, showcasing various color variations. These evolved color patterns present a fascinating trait crucial for understanding their evolution. However, studying these patterns poses challenges, given the intricate nature of colors in the natural world. While past researchers have explored beetle color patterns, quantifying colors requires costly equipment and sophisticated software. This paper introduces an alternative approach, utilizing digital images to examine color variability among Coleopterans. Forty-eight specimens from Mindanao, Philippines, were collected and photographed under consistent conditions. Subsequently, the images were calibrated and processed in R software to calculate image distances through cluster analysis. The results reveal that beetle color patterns fall into two categories: a dark color with deeper shades of gray and a moderately bright tone featuring a slight reddish hue with noticeable yellow highlights. Chrysochroa fulminans is the most distinct beetle across Coleopteran species due to its vibrant green coloration. Family-specific examination of color patterns revealed species with distinct color, Anomala flavipennis and A. smaragdina (Scarabaeidae), Otiorhynchus pauxillus (Curculionidae), Uloma culinaris (Tenebrionidae), and Nupserha fricator (Cerambycidae). The study's findings offer valuable insights into the evolution of Coleopterans, mainly their color patterns, serving as a valuable tool for classification.